2006
DOI: 10.1191/1740774506cn150oa
|View full text |Cite
|
Sign up to set email alerts
|

Problems in comprehension of informed consent in rural and peri-urban Mali, West Africa

Abstract: This study illustrates potential areas of miscomprehension in the consent process in a developing country. The degree of miscomprehension found in this study appeared to be more than that found in similar studies conducted in industrialized nations. Despite efforts to obtain truly informed consent, several factors make it more challenging in the developing world. This research highlights the need for more comprehensive studies of consent in developing countries. Such studies may eventually aid investigators in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
113
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 16 publications
(6 reference statements)
4
113
0
1
Order By: Relevance
“…Risk was the concept least well understood in the previous study of understanding in Mali and was also poorly understood by oncology patients in the United States. 20,22 More than 90% of participants at all sites correctly answered the question regarding withdrawal of consent. This contrasts with other studies indicating that participants in the developing world are more likely to feel pressured into enrolling into research, 12,23 and often have a poor understanding of their right to withdraw.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk was the concept least well understood in the previous study of understanding in Mali and was also poorly understood by oncology patients in the United States. 20,22 More than 90% of participants at all sites correctly answered the question regarding withdrawal of consent. This contrasts with other studies indicating that participants in the developing world are more likely to feel pressured into enrolling into research, 12,23 and often have a poor understanding of their right to withdraw.…”
Section: Discussionmentioning
confidence: 99%
“…For example, another study of understanding among participants in a different malaria vaccine trial in Mali resulted in correct answers to multiple choice questions by between 7% and 73% of participants. 20 A study of parents of child participants in a South African tuberculosis vaccine trial whose authors judged its results "encouraging" showed correct recall between 37% and 85% of the time. 21 Likewise, a cross-sectional survey of participants in 73 different Phase 1, 2, and 3 oncology trials in the United States revealed widespread confusion about the purpose, procedures, and risks of trial participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Studies conducted with research participants, however, suggest that understanding often is incomplete. [7][8][9][10] Some participants are unaware they are enrolled in research, [11][12][13] and others, both in US and international projects, misunderstand risks and the ability to withdraw. [8][9][10] Randomization and placebo, critically important concepts to understand in clinical trials, are particularly likely to be misunderstood.…”
mentioning
confidence: 99%
“…[7][8][9][10] Some participants are unaware they are enrolled in research, [11][12][13] and others, both in US and international projects, misunderstand risks and the ability to withdraw. [8][9][10] Randomization and placebo, critically important concepts to understand in clinical trials, are particularly likely to be misunderstood. 7,14,15 Concerned about inadequate understanding, studies have examined whether consent form length or complexity may hinder understanding of key information.…”
mentioning
confidence: 99%